2020
DOI: 10.21203/rs.3.rs-128951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Genes Targeted in South African Merino and Afrino Sheep Populations Under Long-Term Selection for Reproduction and Body Weight

Abstract: Background: Reproductive performance and body weight are of the utmost economic importance in determining the efficiency of sheep production. Simultaneous selection for increased reproductive performance and early growth traits is a common strategy in many flocks, but ambiguous results regarding the relationship between reproduction and body weight have been reported. The objective of this study was to perform a genome-wide association study (GWAS) in two South African Merino flocks and an Afrino sheep flock t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…For AFR, FGF12, a candidate gene for hair follicle development ( Lv et al, 2020 ) and reproductive traits ( An et al, 2018 ), and ICA1 and NXPH1 , associated with metabolic pathways ( Akanno et al, 2018 ), were some of the key candidate genes identified. Although the AFR is predominantly selected or weighted for meat quality traits, the breed was established as a white-woolen breed for use as a terminal sire when crossed with Merino ewes ( Synman, 2014 ) in response to the presence of kemp (coloured fibre) in crosses of Merino ewes with mutton breeds. The signature for hair follicle development might be a reflection of this selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For AFR, FGF12, a candidate gene for hair follicle development ( Lv et al, 2020 ) and reproductive traits ( An et al, 2018 ), and ICA1 and NXPH1 , associated with metabolic pathways ( Akanno et al, 2018 ), were some of the key candidate genes identified. Although the AFR is predominantly selected or weighted for meat quality traits, the breed was established as a white-woolen breed for use as a terminal sire when crossed with Merino ewes ( Synman, 2014 ) in response to the presence of kemp (coloured fibre) in crosses of Merino ewes with mutton breeds. The signature for hair follicle development might be a reflection of this selection.…”
Section: Discussionmentioning
confidence: 99%
“…The signature for hair follicle development might be a reflection of this selection. ICA1 and NXPH1 , on the other hand, are signatures of the intensive selection weight put on the AFR for meat traits ( Synman, 2014 ).…”
Section: Discussionmentioning
confidence: 99%